A Structured Mesh Generation Tool for CFD Simulations in Process Metallurgy - Zhang, Jiangshan; Liu, Yuhong; Qin, Bangming; Li, Dongyue; Yang, Shufeng; Liu, Qing (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2023)
A mesh generation tool, Script-Meshing, is developed to simultaneously generate geometry and structured mesh for metallurgical vessels using Python scripts and OpenFOAM software. It is demonstrated for several designs and quality meshes are obtained. The parametric modelling and meshing method allow quickly adjusting decomposition arrangement and re-meshing geometry updates. A tundish model is built for CFD validation. The tool is potential to largely expedite the structured meshing and CFD simulation process.